2011
DOI: 10.1186/1472-6963-11-319
|View full text |Cite
|
Sign up to set email alerts
|

How much time do nurses have for patients? a longitudinal study quantifying hospital nurses' patterns of task time distribution and interactions with health professionals

Abstract: BackgroundTime nurses spend with patients is associated with improved patient outcomes, reduced errors, and patient and nurse satisfaction. Few studies have measured how nurses distribute their time across tasks. We aimed to quantify how nurses distribute their time across tasks, with patients, in individual tasks, and engagement with other health care providers; and how work patterns changed over a two year period.MethodsProspective observational study of 57 nurses for 191.3 hours (109.8 hours in 2005/2006 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
261
8
30

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(317 citation statements)
references
References 30 publications
18
261
8
30
Order By: Relevance
“…An Australian study (26) showed that the time spent in transit by nurses (time between activities and patient care), over a three-year investigation, showed a reduction from 7.4% to 4.6%, after optimization strategies. (22) , 11.3% (8) , 11.5% (5) and 18.4% (20) .…”
Section: Discussionmentioning
confidence: 99%
“…An Australian study (26) showed that the time spent in transit by nurses (time between activities and patient care), over a three-year investigation, showed a reduction from 7.4% to 4.6%, after optimization strategies. (22) , 11.3% (8) , 11.5% (5) and 18.4% (20) .…”
Section: Discussionmentioning
confidence: 99%
“…Several reports and studies showed that the vast majority of nurses are too busy to talk to patients because they are over-worked. Westbrook et al (2011) indicated that time in professional relationship is around 37% of nurses' time. It's worth mentioning that almost 25% of this figure belongs to direct care such as bathing, applying dressings and …, so it may be concluded that only a few hours may remain for therapeutic relationship.…”
Section: Resultsmentioning
confidence: 99%
“…It's worth mentioning that almost 25% of this figure belongs to direct care such as bathing, applying dressings and …, so it may be concluded that only a few hours may remain for therapeutic relationship. 43 Disproportion between the nurses' working time with the time needed for therapeutic relationship causes the therapeutic relationship not to be formed and so it causes that nurses do not priorize the visit to patients among their routine activities. 25,44 In this regard, studies have also shown that noncompliance with nurse-to-patient staffing ratios brings about adverse effects on the health condition of patients.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 142 papers were excluded based on the title and abstract, leaving 93 full-text papers to be screened for eligibility. Of these, 75 papers were excluded as they did not fit the inclusion criteria and two papers were unobtainable, even though interlibrary requests were submitted and the authors were contacted, leaving 16 papers [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] included in the review ( Table 9). …”
Section: Health Economic Study Methods and Resultsmentioning
confidence: 99%